2017
DOI: 10.1002/adfm.201606040
|View full text |Cite
|
Sign up to set email alerts
|

Oil‐Impregnated Nanoporous Oxide Layer for Corrosion Protection with Self‐Healing

Abstract: The major drawback of current passivation techniques for preventing corrosion is the lack of ability to withstand any external damages or local defects. In this study, oil‐impregnated nanoporous anodic aluminum oxide (AAO) layers are investigated to overcome such limitations and thus advance corrosion protection. By completely filling hydrophobized nanopores with oil via a solvent exchange method, a highly water‐repellent surface that prevents the penetration of corrosive media into the AAO layer and hence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 65 publications
0
67
0
Order By: Relevance
“…Superhydrophobic materials and surfaces [1][2][3][4] have attracted great interest because of their extreme water-repellent surface property for many potential applications including self-cleaning [5][6][7], hydrodynamic friction reduction [8][9][10], anti-icing [11][12][13][14], anticorrosion [15][16][17][18], biotechnology [19][20][21], thermal systems [22][23][24][25], and micro-and nanodevices [26][27][28]. In particular, previous works on the use of superhydrophobic surfaces as anti-icing coatings have demonstrated that superhydrophobic surfaces have the capability to reduce or even prevent the accumulation and formation of snow and ice on hard solid surfaces [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic materials and surfaces [1][2][3][4] have attracted great interest because of their extreme water-repellent surface property for many potential applications including self-cleaning [5][6][7], hydrodynamic friction reduction [8][9][10], anti-icing [11][12][13][14], anticorrosion [15][16][17][18], biotechnology [19][20][21], thermal systems [22][23][24][25], and micro-and nanodevices [26][27][28]. In particular, previous works on the use of superhydrophobic surfaces as anti-icing coatings have demonstrated that superhydrophobic surfaces have the capability to reduce or even prevent the accumulation and formation of snow and ice on hard solid surfaces [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting at high mechanical durability, various metals, such as stainless steel and aluminum have also been utilized as substrates for LISS by using different surface roughening strategies. Particularly, tungsten oxide films have been deposited on steels by electrodeposition, followed by surface modification and lubrication to obtain LISS, which represents so far the most durable coating substrates for LISS.…”
Section: Development Of Bioinspired Slippery Surfacesmentioning
confidence: 99%
“…Slippery liquid infused porous surface (SLIPS): 15 After anodization and modification with PFDS, fluorocarbon lubricant (Krytox GPL107) was infused onto the porous surface of aluminum with a solvent exchange method. The prepared aluminum sheet with porous Al 2 O 3 structures was immersed in ethanol, after 10 min, the sample was immediately immersed in Vertrel XF for 10 min, and then the sample was immersed in fluorocarbon lubricant for 20 min.…”
Section: Fabrication Of Shs and Slipsmentioning
confidence: 99%
“…When the fluorocarbon lubricant was infused into the rough surface with solvent exchange method, the rough surface of adonic aluminum oxide acted as a reservoir to ensnare the fluorinated lubricant to form a smooth, transparent and static SLIPS on the aluminum substrate. 15 Fig. 4 shows the water CA of a water droplet on SLIPS, owing to the low surface energy of fluorinated lubricant oil, the water CA of the sample increased from 70°to 120°.…”
Section: Xps and Wettabilitymentioning
confidence: 99%